THE EFFECT OF THE PROJECT BASED LEARNING MODEL USED BY CANVA ON THE LEARNING OUTCOMES OF GRADE X MIA STUDENTS OF SMA PARULIAN 2 MEDANACADEMIC YEAR 2023/2024 - Harapan Panjaitan (Jurnal Edukasi dan Pembelajaran STEM, 2025)
The purpose of this study was to determine the effect of Canva Assisted Mission Based Learning Version on students' Physics learning outcomes on the Measurement material of class X Semester I of SMA Parulian 2 Medan in the 2023/2024 Academic Year. This type of research is a quasi-experimental study. The population of this study was all students of class X MIA semester I of SMA Parulian 2 Medan which includes 2 subjects with a total of 30 students. Sampling was carried out by General Sampling where the number of samples was equal to the number of populations, so that the sample in this test changed to 15 students of class X MIA 1 as an experimental model, who were taught to use Canva. Assisted efforts based on the purchase of model information and 15 students of sophistication X MIA 2. as beauty manipulation were taught with a direct introduction model assisted with Canva. The research device used a multiple-desire view at along with 14 items with five choices (a, b, c, d, and e) which had been tested beforehand to determine the validity, reliability, level of difficulty, and item differentiation. Before examining the hypothesis, the normality and homogeneity of the records were checked first. The results show that the general pretest score for the test is 43.20 with a complete deviation of 8.23 and for the ordinary one is forty-two.75 with a standard deviation of seven, sixty-four. For preliminary competency tcount = 0.329 and ttable = 2.05. shows that tcount < ttable, then the initial talent of both classes is identical. After getting knowledge about ending, the post-test changed to finished for both lessons and the average trial cost changed to 80.79 with an average difference of 8.68 while for the elegance of manipulation the publication test cost became 72.67 with a current deviation of 8.15. Based on the pre-test homogeneity test, it was obtained Fcount = 1.162 along with Ftable = 2.48. because Fcount (1.162) < Ftable (2.48), then the pretest research fact turned out to be homogeneous, then the publish-check homogeneity test obtained Fcount = 1.213 along with Ftable = 2.48. because Fcount (1.213) < Ftable (2.48) then the post-test research data is homogeneous, then the statistical test (one-tailed t-test) obtained tcount = 2.67 and ttable = 1.70 at a significance level of α = 0.05, with dk as much as 28. Because tcount > ttable, being unique (2.67 > 1.70), this indicates that there may be a very large effect of the Canva Assisted learning-based task version on Physics students gaining knowledge about the results in the problem of interweaving of sophistication X Semester I personal strengths of the Parulian 2 Medan faculty in the 2023/2024 academic year.